Analyzing the influence of financing and governance on cross-sector social partnerships (CSSPs) value creation. A key focus on CSSPs involved in water sustainability in South Africa - Makombore, Lizah (Graduate School of Business (GSB), 2023)
The study contributes to the growing literature on the financing and governance of CSSPs by providing robust evidence of the UMhlathuze Water Stewardship Programme (uWASP), a single case study with explicit financing mechanisms, capabilities, and governance mechanisms for the creation of value of a water sustainable ecosystem. To date, research investigating partnership performance focused on the use of explicit targets, in a multi-actor cross-sector setting incorporating the crucial moderating effects of financing and governance mechanisms has been lacking. Key findings from the study include grant funding from development institutions and private sector companies was identified as the main source of funding for CSSPs; there is a shift from partnership funding to project-based funding in CSSPs involved in water sustainability as the funders preferences changes; partners' strong financial management systems create strong system-wide financial management capabilities in CSSPs; Operational cross-organizational governance structures are used as the main co-ordinating mechanism for CSSPs; there are significant uses of funding in CSSPs involved in water sustainability in South Africa, through short and medium funding mechanisms and cross - cutting operational governance co-value services are produced in CSSPs and perseverance of CSSPs involved in water sustainability despite the lack of consolidated and co-ordinated partnership measurements and the lack of central budgeting mechanisms. Although, the findings are consistent with a pulse check Rethink Pathway for Development framework by Erickson (2017) on cross-sector collaboration, the available data do not permit us to determine whether the adapted framework with the addition of the Pivot Phase and the subsequent creation of latent value in this phase is consistent with the framework's original continuum measurements. Furthermore, relevant governance mechanisms and processes that align to this phase have to be analysed and made provision for in the distribution of the value created by the partnership, including the mutual rights and obligations of different partners, or for any future contingencies that may affect the operation of the partnerships. Hence, it is conceivable that value creation would be stronger still where CSSPs match assets/investments to funding mechanisms and governance structures that are more comprehensive in scope and detail.